2021
DOI: 10.1111/1744-9987.13726
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, management, and prevention of exit site infections in peritoneal dialysis patients

Abstract: Exit site infection (ESI) is a leading complication of peritoneal dialysis (PD), at an incidence of 0.6 episodes per year in the United States, and a major risk factor for catheter removal and peritonitis. An estimated 20% of all peritonitis cases are preceded by an ESI, with up to 50% of Staphylococcus aureus peritonitis associated with ESI. Gram-negative ESIs are less associated with succeeding peritonitis than their gram-positive counterparts, though when present, are associated with a lower peritonitis cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…As expected, the proportion of these patients was relatively high at 27.1%. Gram-positive bacteria were predominant in this study, consistent with findings in previous reports [ 5 , 19 , 33 ]. The details regarding the frequency discrepancy between peritonitis and ESI remain unclear.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As expected, the proportion of these patients was relatively high at 27.1%. Gram-positive bacteria were predominant in this study, consistent with findings in previous reports [ 5 , 19 , 33 ]. The details regarding the frequency discrepancy between peritonitis and ESI remain unclear.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, we recorded an incidence of all-cause peritonitis of 0.20 per patient-year, near the Japanese average, achieving the target recommended by the International Society for Peritoneal Dialysis (ISPD) of 0.40 [ 7 , 32 ]. Between 10 and 20% of all peritonitis cases have been estimated to be preceded by catheter infections, despite variations depending on the type of causative pathogen [ 33 , 34 ]. As expected, the proportion of these patients was relatively high at 27.1%.…”
Section: Discussionmentioning
confidence: 99%
“…9,46 The low use of topical antibiotic exit-site prophylaxis in this study, which was likely a result of the fact that the health authorities in the Scandinavian and Baltic countries do not encourage long-term antibiotic prophylaxis, due to the risk of development of resistant bacterial strains, may also reduce the generalisability to other PD populations, in which antibiotic prophylaxis is more common. The incidence of exit-site infection, which is reported to vary broadly between studies from 0.1 to 1.2 episodes/patient-year, 47 was 0.28 episodes/patient-year in this study. The proportion of peritonitis episodes with a concomitant exit-site or tunnel infection of 10% in this study of appears to be low, as it has been estimated that 20% of all peritonitis episodes and up to 50% of S. aureus peritonitis are preceded by an exit-site infection.…”
Section: Discussionmentioning
confidence: 42%
“…The proportion of peritonitis episodes with a concomitant exit-site or tunnel infection of 10% in this study of appears to be low, as it has been estimated that 20% of all peritonitis episodes and up to 50% of S. aureus peritonitis are preceded by an exit-site infection. 47 In conclusion, the result of the present prospective study of incident CAPD and APD patients demonstrated that older age, higher number of PD bags connected per day, higher body weight and low serum albumin levels at baseline were independently associated with early peritonitis onset. This indicates a possible benefit of incremental PD, which starts with a lower PD dose, but such a strategy should be tested in further studies.…”
Section: Discussionmentioning
confidence: 53%
“…6,17 In a review of the epidemiology of PD catheter exit-site infections, the authors also observed that there are no standard definitions for repeat, relapsing or recurring exit-site infections. 18 While such analogous classifications for PD-related peritonitis are well defined, 19 it would be beneficial for PD nurses to have classifications for PD catheter exit-site infections clearly defined. Serial monitoring and documentation of PD exit-site infections are part of PD nurses’ responsibilities, thus, a recommendation for a photographic record of a PD patient’s exit-site infection in a future guideline would be helpful, as it is quite common practice for monitoring wounds, 20 as mentioned in the 2017 Guidelines.…”
Section: Exit-site Infection Classification and Terminologymentioning
confidence: 99%